Determinants, level and dynamics of the service sector development in Lodz - Stawasz, Danuta (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The paper aims to present changes in the structure of activities undertaken in Lodz, oriented towards the development of the service sector, including creative industries. A well-developed service sector provides a city and its residents with a long-term income increase and – in the case of Lodz – it creates opportunities to overcome industrial monoculture. The paper will present the dynamics of the service sector development in Lodz during Poland’s economic transformation. The conducted analysis will be based on the available statistical data. Many publications and reports related to the socioeconomic situation of the city will be also used for the purpose of the paper. Conclusions will allow to indicate the role and importance of the service sector in the city economy and to determine the competitive position of the city in the European dimension.